The Early Detection and Management of Neuropathic Pain Following Combat Injury. Issue 2 (1st June 2009) - Mercer, SJ; Chavan, S; Tong, JL; Connor, DJ; de Mello, WF
Abstract : The mechanism of injury on the modern battlefield results in a pattern of wounding which is associated with both nociceptive and neuropathic pain. Nociceptive pain is managed using the WHO Analgesic Ladder but neuropathic pain requires the use of co-analgesic drugs, e.g. antidepressants and anticonvulsants. This study was designed to determine the incidence of neuropathic pain within military casualties with limb injuries. From May to November 2007, 50 casualties were interviewed and assessed using the Leeds Assessment of Neuropathic Symptoms and Signs Scale (LANSS) over consecutive weeks. During the first week post injury, 30%of casualties had a LANSS pain score >12, suggesting a neuropathic element to their pain. The early detection (using LANSS) and management of neuropathic pain using robust protocols represent the most effective strategy to address this significant problem.